Analisis Kehadiran Marketplace Terhadap Minat Beli Pada Pelanggan Toko Konvensional Amsal Mart Desa Moroseneng Kecamatan Batanghari Nuban Kabupaten Lampung Timur - Pratama, Yuliano Cahya; Septiana, Nani (Jurnal Manajemen DIVERSIFIKASI, 2022)
This study examines the presence of the Marketplace on buying interest in the customers of the Amsalmart Conventional Store, Moroseneng Village, Batanghari Nuban District, East Lamping Regency by using price indicators, product completeness, convenience, and promotion. Where the development of the company experienced a decline in sales due to the widespread use of online shopping applications on Amsalmart Store customers. the analytical method used is quantitative research. The object of this research is customers who shop at Amsalmart Stores, Moroseneng Village, Batanghari Nuban District, East Lamping Regency. The number of samples is 65 respondents. Data collection techniques using literature study, interviews, observations and questionnaires. Data analysis techniques using SPSS 20 include testing the requirements for testing the instrument requirements, testing requirements for analysis and testing hypotheses. simultaneously the conclusions of the four variables show a significant and significant effect on customer buying interest, so in this journal discusses the presence of Marketplace on buying interest in customers of the Amsalmart Conventional Store, Moroseneng Village, Batanghari Nuban District, East Lamping Regency. . Keywords: Presence of marketplace, price, product completeness, convenience, promotion